2021
DOI: 10.11591/ijeecs.v24.i3.pp1727-1734
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment analysis of Twitter posts related to the COVID-19 vaccines

Abstract: A real threat to the people of the world has appeared as a result of the spread of the Coronavirus disease of 2019 (COVID-19) disease. A lot of scientific and financial support has been made to devote vaccines capable of ending this epidemic. However, these vaccines have become a subject of debate between individuals, as some people tend to support taking vaccines and others rejecting them. This paper aims to create a framework model to classify the sentiment and opinions of individuals that published in Twitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…A machine learning algorithm (ML) is a two-step process, training, and testing dataset. Thus, we need to label some of the tweets with real opinions to be used in the training stage (Alabid & Katheeth, 2021). The labeling process is carried out to determine the category of sentiment that has been obtained, whether the sentiment is positive or negative.…”
Section: Labelingmentioning
confidence: 99%
“…A machine learning algorithm (ML) is a two-step process, training, and testing dataset. Thus, we need to label some of the tweets with real opinions to be used in the training stage (Alabid & Katheeth, 2021). The labeling process is carried out to determine the category of sentiment that has been obtained, whether the sentiment is positive or negative.…”
Section: Labelingmentioning
confidence: 99%
“…The results revealed that linear SVM was given higher accuracy than Kernel SVM. Alabid, &Katheeth [9]used SVM to predict the sentiment analysis for twitter data that are related to social distancing during the COVID-19 pandemic. They used recall, F1, precision, and confusion matrix in order to evaluate the performance of the SVM algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…Finally, it was shown that increasing the training data would increase the performance of the algorithm [9].…”
Section: Related Workmentioning
confidence: 99%
“…The success of artificial intelligence (AI) systems in such analysis depends on the availability of datasets and quality of the included data, however, and pre-processing unstructured data is important step towards acquiring efficient information from medical records using AI techniques [3], [4]. Natural language processing, AI, and machine learning (ML) all have the potential to simplify the use of unstructured data; however, it is unlikely that these systems will ever reach a point at which computers can make decisions in critical cases rather than simply supporting the humans who must make those decisions [5], [6].…”
Section: Introductionmentioning
confidence: 99%